Microsoft visual C# .net programming : from problem analysis to program design - Doyle, Barbara ([S.l.] : Course Technology, 2004)
This text is ideal for a first course in Computer Science using the C# programming language. Written with the student in mind, code is reflected accurately in blue and green throughout the text, and complete programming examples are included in every chapter. End-of-chapter exercises challenge the reader and test knowledge of the key concepts.